(untitled) (Research, Society and Development, 2020)
The objective of this article was to conduct a conjuncture analysis of the poultry production in Brazil, in relation the performance in the international and national markets from the year 2010. The methodological procedures adopted are of a qualitative nature, through the utilization of bibliographic and documentary revision techniques in the broiler production, Brazil stands out as one of the world’s leading producers and is the largest exporter. In the domestic market, production is concentrated mainly in the south and southeast regions, especially, growth in the midwest due to the soybean and corn production, the main ingredients in poultry feed. In laying poultry, Brazil was the fifth largest world producer in 2017, with most of its production destined for the domestic market. The egg production is concentrated mainly in the southeast and south, and has expanded in the states of Tocantins, Acre, Rondônia and Espírito Santo.